The Better Law Construction of Justice in the Implementation of Restorative Justice - Yanto, Oksidelfa; Dadang, Dadang; Alzagladi, Hasan; Widodo, Guntarto; Sari, Nani Widya (International Journal of Law Analytics, 2024)
The purpose of this study is to identify and understand a new legal design to create better justice while implementing restorative justice. Then, understand and comprehend the urgency of synchronization and synergy of law enforcement for the implementation of restorative justice in a criminal act. The research method used in this study uses a normative legal research method using secondary data obtained through literature studies. The study's findings suggest that in order to improve justice for everyone, a new legal framework pertaining to the application of restorative justice must be developed in the future. All of the criminal justice system's subsystems, including the police, prosecutors, and court institutions, are subject to guidelines when the ideas of restorative justice are institutionalized and put into practice as standards in legislation. This can serve as a solid legal foundation for the application of restorative justice, ensuring that legal certainty is attained as the ideals of a state of law in accomplishing the objectives of law that is fair and advantageous in Indonesia.